Protein folding in HP model on hexagonal lattices with diagonals - Shaw, Dipan Lal; Islam, ASM Shohidull; Rahman, M. Sohel; Hasan, Masud (© 2014 BioMed Central Ltd., 2016)
This article was published in the BMC Bioinformatics [© 2014 Shaw et al.; licensee BioMed Central Ltd.] and the definite version is available at :http://dx.doi.org/10.1186/1471-2105-15-S2-S7. The Journal's website is at: http://bmcbioinformatics.biomedcentral.com/articles/10.1186/1471-2105-15-S2-S7